Features of residency training and psychological distress among residents in a Nigerian teaching hospital (2014)
Background. Resident doctors at University College Hospital (UCH), Ibadan, Nigeria, made a series of complaints about inadequate consultant supervision, lack of structure in the training programme and excessive workload. These complaints led to an evaluation of residency training. Objective. To investigate perceptions of the residency training programme and levels of psychological distress among residents. Methods. All 250 resident doctors at UCH were invited to complete questionnaires about their residency training and general health as part of a cross-sectional study. Data were analysed using SPSS 16. Results. A total of 128 residents (51.2%) responded to the questionnaire. Of the respondents, 72% rated their consultant supervision as good and 82.6% rated support from nurses as good; 61.8% had <5 hours of research or private study per week. There was evidence of psychological distress in 48.4% of the respondents, and there was a significant association between psychological distress and the intensity of work (p<0.01) Conclusion. The residency training programme at UCH appears to prioritise service provision over research and education activities. Residents who report high workloads also have high levels of psychological distress. Tackling these issues could improve overall satisfaction with residency training and reduce complaints.